Evaluation of the Antioxidant Activity of Aqueous and Methanol Extracts of Pleurotus ostreatus in Different Growth Stages - González-Palma, Ivette; Escalona-Buendía, Héctor B.; Ponce-Alquicira, Edith; Téllez-Téllez, Maura; Gupta, Vijai K.; Díaz-Godínez, Gerardo; Soriano-Santos, Jorge (Frontiers in Microbiology, 2016)
Total polyphenols and flavonoids contents, as well as ferric reducing antioxidant power (FRAP), metal ions chelating activity, reducing power assay and scavenging activity of DPPH and ABTS radicals in aqueous and methanolic extracts obtained from mycelium, primordium and fruiting body of Pleurotus ostreatus in both fresh as dry, were evaluated. The total polyphenol content of dried samples was higher in aqueous extracts obtained both in room temperature and boiling. The total polyphenol content of the fresh samples obtained at room temperature and boiling was higher in aqueous extract of mycelium and in the methanolic extract of the fruiting body. In general, flavonoids represented a very small percentage of the total polyphenol content. The antioxidant activity measured by the FRAP method of extracts from fresh samples were higher with respect to the dried samples. The results of the metal ion chelating activity indicate that all extracts tested had acted. Reducing the power of all samples was concentration dependent. In general, the extracts of dried samples showed higher reducing power than the extracts of fresh samples and tend to show greater reducing power by aqueous than methanolic extracts. It was observed that the DPPH and ABTS radical scavenging activities were positively correlated to the concentration of the extract. The results suggested that antioxidant activity could be due to polyphenols, but mainly by different molecules or substances present in the extracts. Overall, the fruiting body of Pleurotus ostreatus showed the best results and the possibility of continuing to investigate its functional properties of this fungus is opened. This is the first report where the antioxidant activity of Pleurotus ostreatus in different growth stage was reported.